NOOTROPE MEDICATIONS FOR COGNITIVE DISORDERS CORRECTION IN CHILDREN WITH EPILEPSY - S.V. Balkanskaya; V.M. Studenikin; L.M. Kuzenkova; O.I. Maslova; A.Yu. Tomilova ("Paediatrician" Publishers LLC, 2007)
The paper presents the results based on the experience of pant ham (hopantenic acid) application, in treatment of 21 patients aged 7-8 years, suffering from benign childhood epilepsy with centroctemporal spikes (rolandic epilepsy), accompanied with impairments of cognitive functions (CF). Utilizing the computer testing systems, basic CF parameters were analyzed before and after the course of pant ham treatment as an add on treatment to basic antiepileptic therapy. Statistically relevant positive effect of the medicine on CF parameters was demonstrated. The authors highly estimate the clinical efficacy of the medication under study. Basic pharmacological and pharmacokinetic properties of hopantenic acid are described.Key words: children, epilepsy, benign childhood epilepsy with centro temporal spikes (rolandic epilepsy), cognitive functions, hopantenic acid.